PENERAPAN BUDAYA ORGANISASI MELALUI PROGRAM ADIWIYATA DI SEKOLAH DASAR ISLAM AS-SHOFA KOTA PEKANBARU - Devi Novita Sipahutar; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Development activities and the rapid advancement of technology have a negative impact on the environment which results in a decrease in quality or environmental degradation. With environmental problems that are increasingly increasing and diverse, it is necessary to have environmental education that is able to change the mindset, attitudes and behaviors that care for the environment. This study discusses the Application of Organizational Culture through the Adiwiyata Program in As-Shofa Islamic Primary School in Pekanbaru City. The purpose of this study is how the application of organizational culture and factors that support the application of organizational culture in As-Shofa Islamic Primary School, Pekanbaru City. This study uses a qualitative method. This research uses Robbins's theory with indicators of individual initiative, integration, management support, supervision and reward systems. The results showed that organizational culture was well implemented in the As-Shofa Islamic Elementary School in Pekanbaru through the adiwiyata program, but there was still a need for an increase in adiwiyata activities at As-Shofa Islamic Primary School in order to win an independent adiwiyata award. Keywords: Adiwiyata Program, Organizational Culture